Incidence and risk of severe infections associated with anti-epidermal growth factor receptor monoclonal antibodies in cancer patients: a systematic review and meta-analysis - Qi, Wei-Xiang (BMC Med, 2014)
BACKGROUND: Anti-epidermal growth factor receptor (EGFR)-monoclonal antibodies (MoAbs) have been widely used in a variety of malignancies. Severe infections (≥grade 3) are potentially life-threatening adverse events with these drugs. However, the contribution of anti-EGFR MoAbs to infections is still unknown. We performed this meta-analysis to determine the overall incidence and risk of severe infections in cancer patients treated with these drugs. METHODS: The databases of PubMed and abstracts presented at oncology conferences and published in the proceedings were searched for relevant studies from January 2000 to May 2014. Summary incidences, relative risks (RRs) and 95% confidence intervals (CIs) were calculated by using either random effects or fixed effect models according to the heterogeneity of included studies. RESULTS: A total of 14,066 patients from 26 randomized controlled trials (RCTs) were included. The use of anti-EGFR-MoAbs significantly increased the risk of developing severe infections (RR 1.34, 95%CI: 1.10 to 1.62, P = 0.003) in cancer patients, but not for fatal infections (RR 1.62, 95%CI: 0.81 to 3.26, P = 0.18). Meta-regression indicated the infections might possibly occur early in the treatment with anti-EGFR MoAbs. On sub-group analysis, the risk of severe infections significantly varied with tumor type (P = 0.001). When stratified by specific anti-EGFR MoAbs, a significantly increased risk of infections with cetuximab was observed (P <0.001), but not for panitumumab (P = 0.98). Additionally, the use of anti-EGFR MoAbs significantly increased the risk of severe infections when used in conjunction with cisplatin (RR 1.48, 95%CI 1.22 to 1.79, P <0.001) or irinotecan (RR 1.53, 95%CI 1.12 to 2.10, P = 0.008). When stratified by specific infectious events, anti-EGFR-MoAbs significantly increased the risk of developing severe sepsis (RR 4.30, 95%CI: 1.80 to 10.27; P = 0.001). CONCLUSIONS: Anti-EGFR MoAbs treatment significantly increases the risk of developing severe infectious events in cancer patients. The risk may vary with tumor types. Clinicians should be aware of the risks of severe infections with the administration of these drugs in cancer patients.